Development and amelioration of green solvent systems for printed mesoscopic carbon perovskite solar cells - CARYS WORSLEY (2023)
Since their advent in 2009, lead halide perovskite solar cells have rapidly progressed to exhibit power conversion efficiencies of 25.5%, approaching that of commercial monocrystalline silicon devices. Although cheap and amenable to solution processing, commercialization is currently limited by poor device stability under operating conditions, prohibitively expensive or toxic components and manufacturing methods unsuitable for large-scale production.Highly stable mesoscopic carbon-based perovskite solar cells (CPSCs) make use of easily scaled screen printing and are frequently described as one of the frontrunners for commercialization. However, significant barriers to commercialisation still exist. For example, the most common precursor solvents, dimethylformamide mixtures and γ-butyrolactone, respectively introduce toxicity and legality issues.This work presents the first application of γ-Valerolactone as a green, non-toxic alternative solvent for CPSC fabrication. Cells fabricated with optimised precursor concentrations and annealing conditions exhibit comparable performance to standard γ-butyrolactone devices, proving that this system is a viable alternative. This will enable continued research in countries where γ-butyrolactone is legally restricted and make large-scale CPSC manufacture more sustainable.This is then ameliorated with the application of green solvent engineering, wherein methanol (MeOH) is used as a solvent additive to improve the performance and reproducibility of GVL precursors. An optimised MeOH proportion of 10% is found to reduce precursor viscosity and improve wetting, as well as promoting more oriented crystal growth and higher quality absorber layers. Stability is also improved, with an unencapsulated MeOH device exhibiting a T80 of >420 hours at 50°C in ambient humidity under AM1.5 illumination.Post crystallisation humidity treatments and age-related performance enhancements are then examined. It is revealed that humidity treatments, required for hysteresis reduction in GBL cells, have no significant impact on GVL-MeOH devices. Age-related performance enhancements are instead found to be a consequence of crystal reorganisation due to slow solvent loss after annealing. Introducing an ambient rest period for completed devices and modules prior to encapsulation is therefore important in maximising device efficiency for these systems.Finally, the factors influencing device infiltration are explored in detail, with the aim of creating a reference resource of methods for targeted infiltration enhancement. A facile, non-destructive method for infiltration analysis is introduced and used to explore the impact of precursor crystallisation, ZrO2 roughness, ink rheology and carbon mesh marking on stack filling. These methods are then applied in well-performing stacks as a tool for general efficiency enhancement, resulting in a champion efficiency of 15% in a 1 cm2 device with the new solvent systems.